2005
DOI: 10.1520/gtj11963
|View full text |Cite
|
Sign up to set email alerts
|

New Method to Determine the True Water Content of Organic Soils

Abstract: The true water content of organic soils is overestimated when the standard oven drying temperature of 110 ± 5°C is used due to some oxidation of the solids, and underestimated when the recommended oven drying temperature of 60°C is used due to some residual pore water remaining in the voids. A new method is presented to identify the precise oven drying temperature for which the mass of the residual pore water exactly balances the loss in the mass of solids due to oxidation. The true water content is calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…Comprehensive descriptions of the geotechnical and hydraulic properties of these materials have been reported for the sewage sludge by O'Kelly (2004bO'Kelly ( , 2005aO'Kelly ( , 2006O'Kelly ( , 2008aO'Kelly ( , 2013b) and the WTR material by O'Kelly (2008bO'Kelly ( , 2014 and Quille (2009, 2010). The oven-drying characteristics of the fraction of the sewage sludge material passing the 425-μm sieve, which had an LOI of 70%, have been reported previously by O'Kelly (2004aO'Kelly ( , 2005bO'Kelly ( , 2005c, employing the same convection oven as that used in the present investigation. The oven-drying characteristics of the coarse fibrous fraction (~10% of the material's total dry mass) retained after wet sieving the bulk material on the 425-μm sieve are investigated in the present study.…”
Section: Test Materialssupporting
confidence: 68%
See 3 more Smart Citations
“…Comprehensive descriptions of the geotechnical and hydraulic properties of these materials have been reported for the sewage sludge by O'Kelly (2004bO'Kelly ( , 2005aO'Kelly ( , 2006O'Kelly ( , 2008aO'Kelly ( , 2013b) and the WTR material by O'Kelly (2008bO'Kelly ( , 2014 and Quille (2009, 2010). The oven-drying characteristics of the fraction of the sewage sludge material passing the 425-μm sieve, which had an LOI of 70%, have been reported previously by O'Kelly (2004aO'Kelly ( , 2005bO'Kelly ( , 2005c, employing the same convection oven as that used in the present investigation. The oven-drying characteristics of the coarse fibrous fraction (~10% of the material's total dry mass) retained after wet sieving the bulk material on the 425-μm sieve are investigated in the present study.…”
Section: Test Materialssupporting
confidence: 68%
“…For instance, the ASTM standard test method for water content determinations on soil and rock (ASTM D2216; ASTM, 2010) states that, for fibrous peat and other highly organic soils, it may be desirable to use a lower ovendrying temperature of 60°C or, alternatively, use desiccators at ambient laboratory temperature. However, since the specimen dry mass is a function of oven temperature, water contents determined in these studies will be lower than values determined for the drying temperature range 100-110°C on account of reduced potential for charring and oxidation of susceptible organic matter, but also because significant amounts of residual pore water can remain within the test specimen (O'Kelly, 2004a(O'Kelly, , 2005b(O'Kelly, , 2005c(O'Kelly, , 2005d. Hence, what is potentially lost by this inconsistency in oven temperature values adopted is the ability to meaningfully compare reported values of water content, especially for sensitive materials.…”
Section: Oven-drying Temperaturementioning
confidence: 84%
See 2 more Smart Citations
“…an apparent lower water content value may be deduced instead). For instance, O'Kelly (2005c) showed that the mass of residual pore water in a test specimen of sewage sludge material oven dried at 60°C was greater than the mass loss due to any charring, oxidation and/or vaporisation of susceptible organic matter at 105°C. Further, some WTR materials can have unusual oven-drying behaviour -for example, the mass of alum WTR test specimens investigated by O'Kelly (2014b) showed no signs of equilibrating after a 34-d drying period at 105°C.…”
Section: Water Content Determinationsmentioning
confidence: 99%